Semiology Analysis on Sikerei Tattoo in Taileleu Village, Southwest Siberut, Mentawai Island - Sagugurat, Rosli Penji; Aditiawarman, Mac (Fakultas Sastra Universitas Ekasakti, 2019)
This research is entitled